Penerapan Continuity Editing dalam Film Kingsman Karya Metthew Vaughu - Muhammad Fauzan Abdillah; Dani Manesah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The film Kingsman: The Secret Service (2014), directed by Matthew Vaughn, blends various cinematic elements that create a captivating visual experience. One of the key aspects supporting the quality of this film is the effective use of continuity editing techniques. This study adopts a qualitative approach with a literature review method to explore the application of editing techniques in strengthening narrative and character development, as well as enhancing the emotional engagement of the audience. The findings reveal that continuity editing not only maintains visual and spatial continuity in action scenes but also supports the development of the main character, Eggsy, from an ordinary young man to a skilled secret agent. This editing technique plays a crucial role in building tension and immersion, allowing the audience to follow the story clearly without being distracted by camera angle changes or other editing techniques. Overall, the application of continuity editing in Kingsman proves to be effective in creating a cinematic experience that harmoniously integrates action, narrative, and emotion.